Upaya Meningkatan Hasil Belajar Siswa Melalui Penerapan Problem Based Learning Menggunakan Media LKPD Online Pada Materi Polinomial Di Kelas XI 4 SMA Negeri 21 Medan - Nirmala, Timoria Tinna; Wadhani, Hismi; Firmasyah; Rambe, Anita; Rambe , Deliana (Universitas Cokroaminoto Yogyakarta, 2024)
This study aims to Improve Students' Mathematics Learning Outcomes Through the Application of Problem Based Learning Using Quizizz Media on Polynomial Material in Class XI 4 of SMA Negeri 21 Medan. This type of research is Classroom Action Research (CAR) which is carried out in 2 cycles with the following stages: planning, implementation of actions, observation, and reflection. The research instruments used are Student Observation Sheets and Knowledge Test Sheets on Polynomial material. The research data were analyzed qualitatively using the percentage of classical learning outcome completion. Based on the results of the research conducted, it can be concluded that using the Problem Based Learning learning model can improve students' learning outcomes on polynomial material in class XI 4 of SMA Negeri 21 Medan. This can be seen from the presentation of completion in the pre-cycle of 5.7% to 54.28% in cycle I, then increasing to 82.85% in cycle II. Based on the results of the Classroom Action Research (CAR), it shows that the use of Quizz media can improve the learning outcomes of class XI 4 students of SMAN 21 Medan on Polynomial material.